Implementing E-Commerce for the Future - U.M.D.B.Alahakoon; S.M.T.N. Samarakoon; S.M.K.P.K. Sakalasooriya; Y.G.I.S. Wickramanayake; D. I. De Silva; Dulanji Cooray (International Journal of Engineering and Management Research, 2022)
This research paper describes an E-commerce web application. There we introduced four stakeholders and assigned related functions to them. The system is based on four stakeholders as user management administrator, store administrator, delivery administrator and customer. This system has been introduced based on buying and selling as grants. It is possible to carry out the usual process without any blockage through this system. Here, the user management administrator performs tasks related to user management, the store administrator performs the functions required to handle the online store, the delivery administrator performs the processes related to the delivery service, and the customer performs the tasks related to the purchase of items.